Penentuan Paket Promosi Pakaian PT. D&C Production dengan Menggunakan Algoritma FP-Growth - Muhammad Rizky; Azhari Ali Ridha; Kamal Prihandani (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
PT. DC Production is a center for selling, foam mattresses, mattresses of all sizes and models, may types of car accessories and various kinds of women's and men's underwear. Problems regarding the decline in sales resulted in the accumulation of goods so that it became a loss. Data mining can be a solution to overcome these problems. This study will use the fp-growth algorithm to form an association model with the aim of helping companies increase their sales by creating underwear promotional packages. The data set that will be used to support this research is the sales transaction data set for the period April 2020 to December 2020. The results show that known rules have been obtained using the fp-growth algorithm, where the rules of this association can create strategies to increase clothing sales. In the form of five association rules that are ready to be used for making clothing promotional packages by meeting the support values and confidence values that have been set at the beginning, namely having a confidence value above 80% and a support value above 25%